Solidarity in Europe : the history of an idea - Stjernø, Steinar (Cambridge University Press, 2005)
Steinar Stjernø examines the concept of solidarity in European politics, tracing its use by social theorists and politicians since the nineteenth century. This unique book systematically compares the many different conceptions of this central political idea held by Europeans over the past two centuries.